It Is Time to Re‐Evaluate the Peer Review Process for Preclinical Research. (11th December 2017) - Bhattacharya, Rajat; Ellis, Lee M.
Abstract : Problems in peer review, the backbone of maintaining high standards in scientific publishing, have led to wide spread discontent within the scientific community. Training in the peer review process and a simpler format to assist in decision making are possible courses to improve and expedite the process of peer review and scientific publishing. Abstract : The authors discuss problems in the peer review process focusing on challenges related to major revisions and reviewer's wish list of experiments; this leads to the loss of time and money. Major revisions rarely lead to significant improvements, while simultaneously delay the dissemination of knowledge. The authors propose simple solutions including training peer reviewers to improve the peer review system.